2011
DOI: 10.1091/mbc.e10-07-0617
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α mRNA: a new target for destabilization by tristetraprolin in endothelial cells

Abstract: The study provides new evidence that the mRNA-destabilizing protein Tristetraprolin is a modulator of HIF-1α mRNA turnover and may contribute to the control of HIF-1α and HIF-1α target gene expression during the adaptive response of endothelial cells to hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 51 publications
(67 reference statements)
11
72
0
Order By: Relevance
“…S4A), which is consistent with the reported differential effects of hypoxia on mRNA levels for HIF-2␣ and HIF-1␣ in HUVEC (Fig. 3D) (29) as well as other cell types (39). Importantly, Dicer overexpression in the setting of hypoxia significantly blunted the luciferase activity of chimeric HIF-2␣ and HIF-1␣ 3Ј-UTR reporters ( Fig.…”
Section: Dicer-dependent Regulation Of Hif-␣ Isoforms and Hypoxiarespsupporting
confidence: 88%
See 2 more Smart Citations
“…S4A), which is consistent with the reported differential effects of hypoxia on mRNA levels for HIF-2␣ and HIF-1␣ in HUVEC (Fig. 3D) (29) as well as other cell types (39). Importantly, Dicer overexpression in the setting of hypoxia significantly blunted the luciferase activity of chimeric HIF-2␣ and HIF-1␣ 3Ј-UTR reporters ( Fig.…”
Section: Dicer-dependent Regulation Of Hif-␣ Isoforms and Hypoxiarespsupporting
confidence: 88%
“…Interestingly, Dicer overexpression in chronic hypoxia leads to further decreases in both VEGFR2 protein and especially mRNA. We observed the same effect with HIF-1␣ mRNA (29,39) and luciferase-HIF-1␣-3Ј-UTR construct expression in chronic hypoxia, which are further decreased when Dicer is overexpressed. Thus, we take these data to indicate that even though distinct mRNA species may be differentially up-or down-regulated in hypoxia the loss of Dicer-mediated microRNA repression is nonetheless functionally relevant and important to a broad variety of hypoxiaresponsive genes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In hypoxia, PHD activity is inhibited, leading to increased HIF-1α protein levels (36). However, this mechanism does not sufficiently explain our observation of resolution of HIF-1α expression in prolonged hypoxia, which has also been reported by others (17,37). miRNA-mediated regulation has become a new theory illustrating the resolution of HIF-1α (16).…”
Section: Mir-210 Alleviated Hypoxia-induced Cell Injury and Apoptosismentioning
confidence: 59%
“…HIF-1α is controlled by a series of complex and elaborate mechanisms because of its abovementioned vital function. Several studies have reported an interesting resolution pattern of HIF-1α, which showed that HIF-1α is not continuous, but undergoes a transient increase followed by a decline under hypoxic conditions (16,17). But canonical oxygen-dependent protein degradation mediated by prolyl hydroxylase domain-containing enzymes (PHDs) cannot competently explain this phenomenon (18).…”
mentioning
confidence: 99%